Efektivitas Massage Effleurage dengan Minyak Zaitun dan Alih Baring terhadap Pencegahan Dekubitus pada Pasien Bedrest - Achirman Achirman; Esi Andriani; Yenni Malkis (Malahayati Nursing Journal, 2025)
ABSTRACT Patients undergoing prolonged immobilization or bed rest are at high risk for developing pressure ulcers (decubitus). Decubitus occurs due to continuous pressure, especially over bony prominences. Preventive nursing interventions such as effleurage massage with olive oil and regular repositioning are essential in maintaining skin integrity. This study aims to determine the effect of effleurage massage with olive oil and repositioning on the prevention of pressure ulcers in bed rest. This quantitative study used a pre-experimental design (one-group pretest-posttest). A total of 18 patients were selected using purposive sampling. The intervention included effleurage massage with olive oil and repositioning every 2 hours, administered over four consecutive days, twice a day. Data were collected using skin assessment forms and a pressure ulcer risk scale. Data were analyzed using the Paired t-test. There was a significant reduction in the risk of pressure ulcers after the intervention with effleurage massage and repositioning (p 0.05). Effleurage massage with olive oil and repositioning is effective in preventing pressure ulcers in bedridden patients. This intervention is recommended as a part of preventive nursing care in inpatient wards.  Keywords: Pressure Ulcer, Bedrest, Effleurage Massage, Olive Oil, Repositioning ABSTRAK Pasien bedrest memiliki risiko tinggi mengalami dekubitus akibat tekanan terus-menerus pada area tubuh tertentu. Intervensi keperawatan seperti massage effleurage dengan minyak zaitun dan alih baring secara teratur dapat menjadi strategi efektif dalam mencegah terjadinya dekubitus. Mengetahui pengaruh massage effleurage dengan minyak zaitun dan alih baring terhadap pencegahan dekubitus pada pasien bedrest. Penelitian ini menggunakan desain kuasi eksperimen dengan pendekatan pretest-posttest tanpa kelompok kontrol. Sampel berjumlah 18 pasien bedrest yang dipilih dengan teknik purposive sampling. Intervensi diberikan selama 4 hari dengan frekuensi dua kali sehari. Data dianalisis menggunakan uji paired t-Test. Terdapat penurunan signifikan risiko dekubitus setelah dilakukan intervensi massage effleurage dengan minyak zaitun dan alih baring (p-value 0,05). Massage effleuragedengan minyak zaitun dan alih baring efektif dalam mencegah terjadinya dekubitus pada pasien bedrest. Intervensi ini direkomendasikan untuk diterapkan sebagai bagian dari tindakan keperawatan preventif di ruang rawat inap. Kata Kunci: Dekubitus, Bedrest, Massage Effleurage, Minyak Zaitun, Alih Baring